Pure intelligent monitoring system for steam economizer trips - Basim Ismail F.; Hamzah Abed K.; Singh D.; Shakir Nasif M. (EDP Sciences, 2023)
Economizers; Failure (mechanical); Fault detection; Knowledge acquisition; Learning algorithms; Learning systems; Neural networks; Plant shutdowns; Steam; Thermoelectric power plants; Extreme learning machine; Fault detection and diagnosis systems; Intelligent modeling; Intelligent monitoring systems; Network methodologies; Operational conditions; Operational variables; Thermal power plants; Steam power plants